Sedimentation as a Support Ecosystem Service in Different Ecological Types of Mangroves - Cinco-Castro, Siuling; Herrera-Silveira, Jorge; Comín, Francisco (Frontiers in Forests and Global Change, 2022)
Mangrove vegetation is strongly dependent on the climate, the physicochemical variables of the sediment, and the hydrological dynamics. These drivers regulate the distribution of different mangrove ecotypes and their ecosystem services, so the net sediment accumulation rates in different mangrove ecotypes in Celestun Lagoon, a karstic zone in the NW Yucatan Peninsula, SE Mexico, were estimated. The measurements considering mangrove ecotypes and their spatial variability concerning the lagoon's salinity gradient (inner, middle, and outer lagoon zones) in three climate seasons (dry, rain, and “nortes”) were realized. We registered the structural variables of the forest, interstitial water physicochemical characteristics, and sediment variables that could influence the net sediment deposition. Fringe mangroves are exposed to low hydrodynamism and show the highest sedimentation rate (3.37 ± 0.49 kg m−2 year−1) compared to basin (1.68 ± 0.22 kg m−2 year−1), dwarf (1.27 ± 0.27 kg m−2 year−1), and “peten” (0.52 ± 0.12 kg m−2 year−1) mangroves. The highest sedimentation rate was recorded in the rainy season (0.24 ± 0.08 kg m−2 month−1), while spatially, the highest value was registered in the outer zone (0.44 ± 0.09 kg m−2 month−1). If the extension of each mangrove ecotype is considered, dwarf mangroves have the highest annual sediment accumulation (1,465 t year−1 in 14,706 ha). The structural, physicochemical, and sediment variables of the sites by mangrove ecotype show that dwarf mangroves represent a distinct group from those formed by fringe, basin, and peten mangroves. However, the sedimentation is high in fringe mangroves at the front of the lagoon and diminishes inland where peten mangroves exist. The differences are given by tree density, but salinity, as a proxy variable of the freshwater influence, significantly influences the sedimentation rate. These results indicate that mangroves in karstic environments can have critical roles in confronting climate change, considering water and sediment flows are the basis of sediment accumulation. According to their hydrogeomorphological drivers, conserving, managing, and restoring the mosaic of mangrove ecotypes improves ecosystem services, including mitigation and adaptation to climate change.